Analisis Keamanan Komunikasi VoIP Server Portable Dilengkapi OpenVPN Menggunakan Linux Asterisk - Rapawuli Eko Putro; Indrastanti Ratna Widiasari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Communication is a very important thing, VoIP is one of the supports that is often used to facilitate communication. VoIP is connected to the internet network so that communication can occur, but VoIP is very vulnerable to security problems in communication. It is very easy for eavesdropping to occur by parties who want to know ongoing information for certain purposes, therefore VoIP security must exist, openVPN is one that is often used. With services that are private / private so that the communication network is protected. In this security research, testing is carried out on a VoIP network with a linux asterisk server using a VPN and not using a VPN. With different results on tests of delay, packet loss, jitter. In the test made a phone call that was registered on the voip server so that the call could be made. The call test was carried out several times and for 6 days in order to see if the results produced were as expected because the internet network could also be disrupted by weather condition. The first phone call that was made without using a VPN the results that were obtained were not very good, in contrast to the second phone call that used a VPN the results produced by the analysis were better.